2022
DOI: 10.1021/acs.cgd.2c00308
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structures, H2S, and Iodine Uptake Properties of Four New Coordination Polymers Constructed from Group 12 Transition Metal Ions and a Bidentate Sulfur Donor Ligand

Abstract: In the current work, we have managed to design and synthesize a set of four new sulfur coordination polymers, namely, [ZnCl2(Ls)2] n (1), [CdCl2(Ls)2] n (2), [Cd­(NCS)­(μ2-SCN)2(Ls)2] n (3), and {[Hg­(μ2-Cl)­(Ls)2]­[ClO4]} n (4) using a branch tube method. They have been fully characterized using several techniques including elemental analysis, Fourier transform infrared spectroscopy, powder X-ray diffraction, photoluminescence spectroscopy, UV–vis, and single-crystal X-ray diffraction. Polymer 1 was synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…The coordination of metal to sulfur leads to a red‐shift in the position of this band that appears at 520 and 519 cm −1 for Zn and Hg‐SCP, respectively, which is the best indication for the formation of the sulfur coordination polymers. The very sharp band of υ (CN)–NCS and –SCN co‐ligands are observed at 2070 and 2089 cm −1 in the FT‐IR spectrum of zinc and mercury polymers [ 38 ] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination of metal to sulfur leads to a red‐shift in the position of this band that appears at 520 and 519 cm −1 for Zn and Hg‐SCP, respectively, which is the best indication for the formation of the sulfur coordination polymers. The very sharp band of υ (CN)–NCS and –SCN co‐ligands are observed at 2070 and 2089 cm −1 in the FT‐IR spectrum of zinc and mercury polymers [ 38 ] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…[34,35] Organic ligands with sulfur donor atoms especially heterocyclic thioamides, due to the fact that these ligands exhibit rich and diverse coordination chemistry that encompasses a great number of transition metal compounds, have been continuously attracting the attention of many researchers. [36][37][38][39][40][41][42][43][44][45] Among sulfur donor heterocyclic organic ligands, 1-methyl-3H-imidazole-2-thione [methimazole (MMI)] is an antithyroid medication that is considered the first-line agent for medical therapy of hyperthyroidism. Excessive production of thyroid hormones by the thyroid gland leads to a pathological condition named hyperthyroidism (overactive thyroid).…”
Section: Introductionmentioning
confidence: 99%
“…27,28 In the literature, only a few theoretical and experimental studies on the H 2 S and SO 2 removal by MOFs have been published. [29][30][31][32][33][34] Most of them are recent. Indeed, experimental and computational efforts have been made recently to explore the use of MOFs 35 or natural or synthetic zeolites 36 for the effective removal of SO 2 and H 2 S gases.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they showed that UiO-66, ZIF-71, ZIF-69, and ZIF-97 exhibit good performances for H 2 S separation from air, with selectivity and adsorption capacities higher than 300 mg g −1 and 0.01 mmol g −1 at room temperature and atmospheric pressure, respectively. Besides, Beheshti et al 34 synthesized a set of four new sulphur coordination polymers ( e.g. [ZnCl 2 (L s ) 2 ] n polymer where the ligands L s = 1,1′-(pentane-1,5-diyl)bis(-3-methyl-1 H -imidazole-2-thione)).…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] On the other hand, despite the unique properties of sulfur based compounds in the capture of iodine, there are few investigations of iodine removal by sulfur based COFs, MOFs and CPs, so there is still a long way to go. [47][48][49][50] In light of these pieces of information and the exploration of our previous work on sulfur coordination polymers for the removal of iodine, in the current paper we have synthesized three novel Hg-CPs based on a sulfur containing Ls ligand [Ls = 1,1-bis(3-methyl-4-imidazoline-2-thione)methane]. Considering that the liver has the main function in detoxification in the human body, we have also studied the cytoprotective effects of the title ligand against mercury chloride toxicity using the MTT assay.…”
Section: Introductionmentioning
confidence: 99%